1996
DOI: 10.5144/0256-4947.1996.625
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococci (VRE) as Normal Flora of the Intestine in Patients at a Tertiary Care Hospital

Abstract: There has been a rapid increase in the incidence of infection and colonization with vancomycin-resistant enterococci (VRE) in American and European hospitals in the last six to seven years, with fecal carriage reported to be as high as 86% on some services. In order to determine the frequency of VRE as normal flora of the intestine in Saudi patients, microbiological analysis of stool specimens from 4276 patients from a tertiary care referral hospital was performed. VRE, identified as Enterococcus faecium, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…), Czech Republic (Kolar et al . ) and Saudi Arabia (Qadri and Postle ). The highest documented VRE colonization rates occur in Palestine (Hijazi et al .…”
Section: Discussionmentioning
confidence: 99%
“…), Czech Republic (Kolar et al . ) and Saudi Arabia (Qadri and Postle ). The highest documented VRE colonization rates occur in Palestine (Hijazi et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 4276 patients from a tertiary care referral hospital, VRE was identified in only six (0.14%) patients. 18 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only six cases of VRE infections and some colonization have been seen or reported. 4,5,7,10 As the prudent use of antimicrobials by clinicians is effective in lowering the emergence of resistant isolates in humans, animal husbandries and poultry farms should be discouraged to use avoparcin and other antimicrobial agents as feed supplement, in order to minimize acquisition of resistant flora.…”
Section: Discussionmentioning
confidence: 99%